Pengembangan Projek Penguatan Profil Pelajar Pancasila Pada Pengolahan Sampah Dapur di Kelas 2 Sekolah Dasar - Charlalianthy Hiellary Liuw; Juliana Margareta Sumilat; Deysti Trifena Tarusu (Peneliti.net, 2023)
Characteristics of the Pancasila Student Profile are Indonesian students who are faithful, devoted to God Almighty, and have noble character. These are students who have morals in their relationship with God Almighty. Students who reason critically are able to objectively process both qualitative and quantitative information, build relationships between various information, analyze information, evaluate and conclude. In the odd semester of the 2022/2023 academic year, data for class 2C students at SD Inpres Mapanget Barat. In the learning project for strengthening the Pancasila Profile. Sustainable with the learning focus being making liquid compost and planting plants. The methodology used in this activity is that the author uses a mentoring method by carrying out inculturation and building trust with the community, so that an equal and mutually supportive relationship is established. Timeline is a technique for tracing the historical flow of a society by exploring important events that have been experienced in a certain time line. In implementing the project to strengthen the profile of Pancasila students, in this case making liquid compost and planting plants, the student grades were obtained as follows: The average class score in the Assessment of the Pancasila Student Profile Project at SD Inpres West Mapanget in the process of making liquid compost and planting plants was obtained as follows. as follows: class II C obtained an average score of 79.30.